PELAKSANAAN FUNGSI LEGISLASI DPRD KOTA SEMARANG PERIODE 2009 - 2012 (Perda Inisiatif DPRD Kota Semarang) - Prastyo Utomo (Journal of Politic and Government Studies, 2013)
ABSTRACTIn the exercise of the legislative function as one of the functions carriedlegislature Semarang City Council area only a few produce Regulation (Regulation) derivedfrom Parliament initiative. In other words, less Semarang City Council initiative. The role ofparliament dominated just about researching and reviewing the Commission's draft proposalexecutive level. Mechanism Lawmaking in Semarang used by Parliament as a legislativebody is through the submission stage of submission of draft legislative proposals later in theplenary session by the Chairman of the Board and waiting for answers as well as delivery ofthe faction, further discussion on the Commission's later decision after the plenary sessionand disampaiakan to the executive. Making laws that occurred in the city of Semarang is aproposal from the legislature despite Semarang City Council Bylaw only produce less thanthe executive so that the Legislastif often stand in the discussion, assessment, decisionmaking,setting together, but were not involved in the enactment of Parliament since thepromulgation of regulations is the duty of the Regional Secretary of Semarang.Obstacles to Implementation of Legislation Function Semarang City Council for the2009-2012 term: Still the lack of ability of the Semarang City Council in lawmaking, theexecutive dominance higher than the Legislature, Semarang City Council agenda that feelssolid, is still a lack of regulations implementing the legislation complete, The charge interestof certain groups in the preparation of draft by the Semarang City Council.Keywords: Decentralization, Parliament, Legislative Functions